Predisposing, enabling, and need factors of service utilization in the elderly with mental health problems - Volkert, Jana (International psychogeriatrics, 2018)
ABSTRACTBackground:Empirical data on the use of services due to mental health problems in older adults in Europe is lacking. The objective of this study is to identify factors associated with service utilization in the elderly. - METHODS: As part of the MentDis_ICF65+ study, N = 3,142 people aged 65-84 living in the community in six European and associated countries were interviewed. Based on Andersen's behavioral model predisposing, enabling, and need factors were analyzed with logistic regression analyses. - RESULTS: Overall, 7% of elderly and 11% of those with a mental disorder had used a service due to mental health problems in the last 12 months. Factors significantly associated with underuse were male sex, lower education, living in the London catchment area, higher functional impairment and more comorbid mental disorders. The most frequently reported barrier to service use was personal beliefs, e.g. "I can deal with my problem on my own" (90%). - CONCLUSION: Underutilization of mental health services among older people in the European community is common and interventions are needed to achieve an adequate use of services.
Published online: 04 December 2017
Gesehen am 27.03.2019